Finite temperature behavior of gas phase neutral Au-n (3 <= n <= 10) clusters: a first principles investigation - De, Himadri Sekhar; Krishnamurty, Sailaja; Mishra, Deepti; Pal, Sourav (Journal of Physical Chemistry C, 2011)
{Relativistic density functional theory (DFT) based molecular dynamical simulations are performed on gold clusters with 3-10 atoms (Au-n

First principle investigation on the thermal stability of a golden fullerene: a case study of Au-32 - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Catalysis Today, 2012)
Structural and electronic properties of Au-32 cluster are analyzed using relativistic density functional theory (DFT) based methods. Further, DFT based molecular dynamical (MD) simulations are performed on Au-32 golden fullerene with an aim of understanding its thermal stability at various working temperatures. Various conformations being populated at different temperatures of a cluster are analyzed. The study shows that the ground state icosahedral conformation is stable only up to 300 K and structure remains in a hollow conformation only up to 400 K. This clearly explains the reasons for failure by experimentalists in trapping the unique fullerene conformation in spite of the theoretical predictions of it being a very stable one. The above MD study also indicates that the bare fullerene Au-32 cluster (without any stabilizing ligands) can be used for potential catalytic applications only around room temperatures. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Au-32 cluster; Born-Oppenheimer molecular dynamics; Density functional theory; Golden fullerenes; Relativistic effects

Finite temperature behavior of carbon atom-doped silicon clusters: depressed thermal stabilities, coexisting isomers, reversible dynamical pathways and fragmentation channels - Joshi, Krati; Maibam, Ashakiran; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Silicon carbide clusters are significant due to their predominant occurrence in meteoric star dust, particularly in carbon-rich asymptotic giant branch stars. Of late, they have also been recognized as nanoclusters with potential applications in technology. Them both being elements of the same group, there is excellent potential for precise control over the physico-chemical properties of such molecular length-scale materials through atomic engineering and this has been explored recently by various experimentalists. This report simulates one of the significant physical properties, viz. conformational stability, of various carbon-doped silicon clusters as a function of temperature using Born-Oppenheimer molecular dynamics methodology. Single carbon atom-doped silicon clusters with 4-9 atoms (i.e., Si3C-Si8C) are chosen for this study as the gas phase geometries of these clusters have been characterized using a combination of experimental and theoretical methods in the recent past. The simulations ratify that various conformations do not interconvert among themselves at 300 K. The interconversion occurs at 500 K or above, thereby ratifying the possibility of the coexistence of multiple conformations of a given cluster, which are generally synthesized under subroom temperature conditions. Furthermore, the above single carbon atom-doped silicon clusters: (a) have depressed thermal stabilities as compared to their pristine counterparts with the exception of a Si5C conformation; (b) undergo multifarious evolution of the cluster, through the reversible dynamical and fragmentation pathways as a function of temperature and (c) single carbon atom-doped silicon clusters with 7 atoms (starting from Si6C) and above undergo a fragmentation at nearly 2000 K. The underlying electronic and structural properties of various clusters are discussed to explain the above observations with a note on critical fragmentation energy barriers required for the segmentation of clusters with seven or more atoms.

Facile fabrication of nano silver phosphate on B-doped g-C3N4: an excellent p-n heterojunction photocatalyst towards water oxidation and Cr (VI) reduction - Sahoo, Mitarani; Babu, Pradeepta; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
A photostable Ag3PO4/BCN type-II p-n heterojunction has been demonstrated by loading nano Ag3PO4 on B-doped g-C3N4 nanosheet (BCN). The photocatalysts were successfully characterized by various physicochemical techniques and their photocatalytic activities were tested towards the water oxidation reaction to produce oxygen and Cr (VI) reduction under visible light. The HRTEM confirms Ag3PO4 with a particle size of 15 nm has been deposited on BCN to construct a p-n heterojunction. The BCNS-50 absorbs more visible light in the solar spectrum as compared to other catalyst, demonstrating the ability to generate 587 mu mol h(-1)g(-1) O-2 and reduces 98% of 20 ppm Cr (VI) solution in 1 h. The lower PL intensity as well as lower arc value in case of BCNS-50 suggests the maximum e-h separation and lower charge transfer resistance across the semiconductor/electrolyte interface. The BCN sheet provides a compact heterojunction where the oxidation peak of Ag3PO4 decreases gradually and disappear in case of BCNS-50 suggesting the enhance stability of Ag3PO4 in the heterojunction. BCNS-50 could able to produce -139 and 3087.5 mu A photocurrent both in cathodic and anodic direction which is approximately 7 and 2.4 folds higher as compared to nano Ag3PO4. The generation of photocurrent in both cathodic and anodic direction confirms the formation of p-n heterojunction which further supported by Mott-Schottky analysis. Furthermore the construction of the p-n heterojunction is verified via Mott-Schottky study. DFT calculation explains the contribution of various atomic orbital of Ag3PO4 and BCN towards the formation of hybrid orbital in the heterojunction and the path for charge delocalization between them. This work may provide a limelight and alternative pathway for enhanced photocatalytic performance on construction of the p-n heterojunction in a simple way. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Cr (VI) reduction; Density functional theory; Interfacial zone; p-n heterojunction; Photocatalyst; Water oxidation

First-principles investigation of the electrocatalytic reduction of CO2 on zirconium-based single-, double-, and triple-atom catalysts anchored on a graphitic carbon nitride monolayer - Hassan, Afshana; Anis, Insha; Shafi, Sadaf; Assad, Assif; Rasool, Anjumun; Khanam, Romana; Bhat, Gulzar Ahmad; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (ACS Applied Nano Materials, 2022)
Conversion of carbon dioxide (CO2) with the help of an appropriate electrocatalyst with high stability, low onset potential, and exceptional selectivity is still one of the great tasks in the electrocatalytic reduction of CO2 to valuable chemicals. Herein, by means of systematic first-principles simulations, we investigate the CO2 reduction reaction (CO2RR) activity of zirconium-based single-, double-, and triple-atom (Zrn@C2N; n = 1-3) catalysts anchored on a graphitic carbon-nitride monolayer. In tune with the Sabatier principle, our results reveal that a moderate CO2 binding is vital for a low onset potential for the CO2RR. Consequently, based on rigorous free energy calculations, the Zr-based single-atom catalyst (SAC) is found to be most effective to convert CO2 to valuable products such as HCOOH and CH3OH. It is worth noting that CO2 reduction to HCOOH is spontaneous via the *HCOO intermediate on Zr1@C2N and involves a low onset potential of -0.23 V with respect to the reversible hydrogen electrode from the *COOH intermediate. Among all the catalysts evaluated computationally, the Zr SAC further reveals the lowest onset potential of -0.89 V for CH3OH formation. The results show that the Zr-based catalysts especially Zr1@C2N are found to effectively suppress the competitive hydrogen evolution reaction and promote the CO2RR. Moreover, all three catalysts exhibit high kinetic and thermal stability with negligible distortion due to which their structures can be retained very well up to 600 K. Thus, the current work may provide effective catalyst-design strategies for enhancing the electrocatalytic CO2RR performance of Zr-based materials.
Keywords: C1 and C2 products; CO2 reduction; first-principles simulations; hydrogen evolution reaction; onset potential; single-atom catalysts (SACs); Zrn@C2N catalysts

Free base phthalocyanine coating as a superior corrosion inhibitor for copper surfaces: a combined experimental and theoretical study - Samal, Pragnya Paramita; Dekshinamoorthy, Amuthan; Arunachalam, Shivakami; Vijayaraghavan, Saranyan; Krishnamurty, Sailaja (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2022)
In the quest of novel, eco-benign copper corrosion inhibitors, free base and a set of six metal Phthalocyanine (Pc) coatings (where metal is Zn, Cu, Fe, Co, Ni, Mn) are systematically evaluated for their corrosion inhibition efficiency. The study demonstrates that the free base Phthalocyanine coatings are superior corrosion inhibitors for Cu surface in HCl with a corrosion inhibition efficiency of 88% as compared to its metal counterparts. A detailed and indepth study involving concerted electrochemical polarisation, impedance measurements at various concentrations of HCl assert the superior corrosion inhibition efficiency of free base Pc coatings as compared to its metal counterparts. Underlying factors/interface chemistry contributing to it is brought out using first principle based studies. First principles based computational studies establish that superior corrosion inhibition ability of free base phthalocyanine molecule is attributed to its innate binding ability with copper surface and its better inter-molecular packing. Thus, the theoretical adsorption trends of various studied phthalocyanine molecules while clearly following the experimental corrosion inhibition efficiency trends undermine the importance of contribution of chelating factors for the formation of a stable and efficient corrosion inhibition coating on a surface and that the adhesion/adsorption strength of a molecule correlates directly to its corrosion inhibition efficiency. The experimental observations are further substantiated through FE-SEM, EDAX and XPS studies. The corrosion inhibition efficiency of free base phthalocyanine is followed by its zinc based counterpart at 85%.
Keywords: Copper surface; Corrosion inhibitors; DFT studies; Impedance; Phthalocyanine coatings

From ``Cosmic Cooking'' to chemistry of the future: a collective dialogue on chemistry as a tribute to Prof. Sourav Pal. - Roy, Soumyajit; Krishnamurty, Sailaja; Schoefberger, Wolfgang (Frontiers in Chemistry, 2022)
Keywords: cosmic cooking; coupled cluster and density functional calculations; dialogue on chemistry; pincers porphyrinoids and oxometalates; small molecule activation; Theoretical chemistry

FeCl2-catalyzed rearrangement of aryl peroxyoxindole into 1,3-benzooxazin-4-One - Mohanta, Nirmala; Samal, PragnyaParamita; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Advanced Synthesis & Catalysis, 2023)
We report an FeCl2-catalyzed radical rearrangement of aryl peroxyoxindoles into 1,3-benzooxazin-2-ones to obtain a variety of aryl substituted 1,3-benzooxazin-4-ones in moderate to good yields. Mechanistically, this skeletal rearrangement of peroxyoxindoles proceeded via radical pathway and was well supported with a series of experimental findings and DFT studies.
Keywords: 1; 3-Benzooxazin-4-one; FeCl2; Peroxyoxindole; rearrangement; Ring expansion

Functionalized Mo2BX2 (X = H, OH, O) MBenes as a promising sensor, capturer and storage material for environmentally toxic gases: A case study of 1T and 2H phase - Shukla, Aarti; Sharma, Gautam; Krishnamurty, Sailaja (Applied Surface Science, 2023)
MBenes analogous to MXenes, exfoliated from the bulk MAB phase (M = transition metal, A = IIIA and IVA group, and B = boron) have appeared as promising two dimensional (2D) materials due to their intriguing properties. Here, we report the 2D 1T-2H-phase of Mo2B with their functionalized derivatives Mo2BX2 (X= H, OH, O) and investigate their structural, electronic, and adsorption behavior of toxic gases using the first-principles calculations. This study finds that pristine and functionalized MBenes have dynamic and thermal stability and possess metallic nature in both phases. Based on adsorption behavior and comparison with other 2D materials, we find that pristine MBenes are a desirable adsorbent for NO2, SO2, and CO2 capture. In contrast, the moderate adsorption energies for functionalized MBenes-NH3 systems reveal good sensitivity for NH3 gas detection in both phases. In particular, 2H-Mo2BH2 has higher CT (-0.11e) and appropriate adsorption energy (-0.30 eV), leads a shorter recovery time. Further, DOS calculations reveal that the electrical conducting behavior of MBenes makes them suitable for NH3 detection with a short recovery time. Our results would provide the first insight into the surface-functionalized effect on the structural and electronic properties of the MBenes, and shed light on the application of MBenes for the sensing and catalyst of typical toxic and greenhouse gases, respectively.
Keywords: Adsorption energy; First-principles study; Functionalization; Gas sensing; MBenes

First-principles simulation of active site selectivity for CO2 and H2 adsorption on Mg(OH)+/Mg2+ and Ca(OH)+/Ca2+ zeolites - Samal, Pragnya Paramita; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2024)
One very effective strategy for addressing global warming and transitioning to sustainable energy sources is selective CO2 separation over H-2. Porous materials, particularly zeolites, have demonstrated enormous potential for energy-efficient separation techniques combined with storage. By altering interactions at cation-binding sites, zeolite's gas adsorption characteristics toward carbon capture can be improved. In this study, Mg and Ca are assessed as extra-framework cations in divalent (Ca2+, Mg2+) and monovalent states (Ca(OH)(+), Mg(OH)(+)) in faujasite and chabazite zeolites for CO2 capture over H-2. The study also explores the impact of mixed cations, viz., a combination of both Ca2+ and Mg2+ in the framework, on their selective adsorption potential. This study uses DFT with dispersion corrections to calculate adsorption energies, enthalpies, and Gibb's free energies of adsorbed CO2 and H-2 molecules. Among the dispersion parameters evaluated, viz., D4, TS/HI, and MBD, D4 approaches experimental accuracy. In general, the adsorption trend obtained for CO2 is Mg FAU > Ca FAU > Mg CHA > Ca CHA > Mg(OH)(+) FAU > Ca(OH)(+) FAU > Mg(OH)(+) CHA > Ca(OH)(+) CHA. The heats of adsorption using PBE+D4 for CO2 are -46 kJ/mol for Ca FAU and -10 kJ/mol for Ca(OH)(+) FAU, respectively. These values closely align with the experimental results of -45 and -6 kJ/mol, respectively, within a chemical accuracy limit of +/- 4 kJ/mol. The relative adsorption energies suggest that for both FAU and CHA, there exists a minimum difference of 26 kJ/mol in adsorption energies between CO2 and H-2. Hence, this piece of work highlights that FAU with Ca and Mg as extra-framework cations in a six-membered cage can be a viable substitute to replace, the current best candidate in literature, viz., Li+, for selective CO2 capture.

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye